INFLUENCE OF TWISTED TAPE INSERT ON OVERALL HEAT TRANSFER COEFFICIENT AND EFFECTIVENESS CHARACTERISTIC OF AUTOMOBILE RADIATOR (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this work, the overall heat transfer coefficient and the effectiveness of a circular tube automobile radiator with aluminium twisted tape insert having three different twist ratio (y = 8, 12, and 16) is investigated experimentally by varying the fluid flow rate and temperature.Â  The results show that the presence of twisted tape inserts increases the overall heat transfer coefficient and the effectiveness compared with the plain tube radiator. The empirical correlations of these parameters were statistically analyzed and optimized using ANNOVA table by implementing Design expert Software.